Arteriovenous supercharging: A novel approach to improve reliability of the distally based sural flap. (July 2021) - Agarwal, Pawan; Sharma, Dhananjaya; Kukrele, Rajeev
Complex soft-tissue defects of the distal third of the leg, foot and ankle with exposed bones/joints, tendons and implants need a flap for their closure. Distally based sural flap is commonly used, but it has a high partial necrosis rate due to venous insufficiency. We addressed this issue with AV supercharging by dorsalis pedis artery with short saphenous vein. Eight patients (seven males, mean age 34.12 years) with post traumatic lower limb defects over heel and foot were included. All flaps survived and healed although four flaps developed superficial partial epidermolysis. Average healing time was 20.12 days. Closure of the AV fistula was not required in any of the patients. At mean follow-up of two months, all patients were ambulatory with well settled flap. Arteriovenous supercharging of distally based sural flap through short saphenous vein improves the distal arterial perfusion in the flap and prevents distal flap necrosis.